Die Auswirkungen von Gewinn- und Entscheidungsbeteiligung auf den Unternehmenserfolg - Kornelius Kraft (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This article summarizes recent studies concerning the effects of organizational change on fundamental economic variables. The framework applied to take account of possible selectivity effects is explained in detail. This methodology is applied to the effects of profits sharing and the legal provisions with respect to worker codetermination rights on the plant and firm level.
Keywords: J53; J54; L25; 330; Gewinnbeteiligung - Auswirkungen; Arbeitnehmerbeteiligung - Auswirkungen; Unternehmenserfolg; Mitbestimmungsgesetz; Selektionskorrektur; Betriebsverfassungsgesetz; Unternehmensorganisation; organisatorischer Wandel; Kapitalbeteiligung - Auswirkungen; Wirkungsforschung; Organisationsänderung; IAB-Betriebspanel